Lentigo maligna melanoma in situ with neurotropism. (6th July 2020) - Occidental, Michael; Shapiro, Richard; Jour, George
Abstract: Perineural invasion, or neurotropism, is defined by the presence of cancer cells either within the neuronal sheath or found along the nerves. In melanoma, it is most commonly associated with invasive desmoplastic melanoma, a melanoma that is most commonly associated with malignant melanoma in situ, lentigo maligna type. Initially, perineural invasion was included in the reported Breslow thickness; however, recent data suggest that it should not be included. In this report, we describe a case of malignant melanoma in situ, lentigo maligna type, with associated neurotropism in the absence of invasive component.